The role of protein acetylation in carcinogenesis and targeted drug discovery - Yang, Jingru; Song, Cong; Zhan, Xianquan (Frontiers in Endocrinology, 2022)
Protein acetylation is a reversible post-translational modification, and is involved in many biological processes in cells, such as transcriptional regulation, DNA damage repair, and energy metabolism, which is an important molecular event and is associated with a wide range of diseases such as cancers. Protein acetylation is dynamically regulated by histone acetyltransferases (HATs) and histone deacetylases (HDACs) in homeostasis. The abnormal acetylation level might lead to the occurrence and deterioration of a cancer, and is closely related to various pathophysiological characteristics of a cancer, such as malignant phenotypes, and promotes cancer cells to adapt to tumor microenvironment. Therapeutic modalities targeting protein acetylation are a potential therapeutic strategy. This article discussed the roles of protein acetylation in tumor pathology and therapeutic drugs targeting protein acetylation, which offers the contributions of protein acetylation in clarification of carcinogenesis, and discovery of therapeutic drugs for cancers, and lays the foundation for precision medicine in oncology.